An agent based approach towards autonomic services - Leong, Khai Weng (2009)
Services play an increasingly important role in software applications today. There are increasing demands to build/compose software as a collection of services. A service in this context may be defined as a behaviour that is provided by a component for use by any other component based on a network-addressable interface contract. Such service oriented software raises some challenges when designed using current object-oriented methodologies in situations where there is a need to trade-off competing goals, where there are complex business workflows, or when service execution is highly dynamic. Multi-Agent Systems (MAS) fits well into complex services, but current Agent-Oriented Software Engineering (AOSE) methodologies do not address the aforementioned challenges of services. AOSE for services that operate in open, dynamic and complex environments such as Grids is a major problem that needs to be addressed. This thesis describes an AOSE methodology that is particularly suited for building service oriented software. It has the advantages of being accessible and pragmatic. The thesis presents a novel Goal-Oriented and FCM for Agent-mediated Autonomic Services (GOFASS) methodology used to specify agents for the agentmediated autonomic services architecture. The GOFASS methodology provides guidance from early requirements gathering through to agent design and implementation.